The relationship between physical appearance perfectionism on subthreshold depression in college students: the role of gender and fear of negative evaluation - Wei, Yiru; Chen, Hong; Sun, Bo; Kong, Lingli (Frontiers in Public Health, 2025)
IntroductionOver the past decades, subthreshold depression has emerged as a significant mental health concern among college students, with prevalence rates reaching 40.8%. Despite its substantial impact on psychological well-being, subthreshold depression often remains overlooked due to its failure to meet clinical diagnostic criteria for major depressive disorder. Moreover, the underlying mechanisms of subthreshold depression remain poorly understood. This study investigates the interplay between appearance perfectionism, fear of negative evaluation, and gender in relation to subthreshold depression among college students.MethodologyVia cross-sectional design, we recruited 820 college students (Mage = 20.78, SD = 2.04) through convenience sampling. Participants completed online questionnaires assessing physical appearance perfectionism, fear of negative evaluation, and depressive symptoms using validated scales. Data were analyzed to examine a moderated mediation model.ResultsOur findings reveal a significant positive correlation between physical appearance perfectionism and subthreshold depression (r = 0.48, p < 0.001). Fear of negative evaluation emerged as a significant mediator in this relationship (t = 5.553, 95% CI = [0.084, 0.194]). Notably, gender moderated the association between appearance perfectionism and fear of negative evaluation, with female students demonstrating a stronger relationship between these variables.FindingsThese results underscore the detrimental effects of appearance-related perfectionism in the context of Chinese cultural norms. The study highlights the importance of addressing both physical appearance perfectionism and fear of negative evaluation in mental health interventions for college students. Educational institutions, families, and society should implement strategies to promote healthy body image perceptions and mitigate the impact of negative evaluation fears. Furthermore, our findings emphasize the need to consider gender-specific approaches, as social expectations and gender role differentiation appear to influence the psychological mechanisms underlying subthreshold depression.